Airway management considerations in patients with vocal fold implants - Shehata, Islam Mohammad; Masood, Waniyah; Daebis, Ahmad; Gamal, Islam; Urits, Ivan; Viswanath, Omar; Cornett, Elyse M.; Kaye, Alan D. (Frontiers in Anesthesiology, 2023)
Vocal fold implants are indicated to manage glottis insufficiency, restore proper vocal cord functioning, and prevent aspiration. Over time, various materials have been used for implants with different physical prosperities. Patients with vocal fold implants (VFI) present challenging airway. There are several considerations that perioperative physicians should recognize when confronting airway management in the setting of vocal fold implants. The preoperative assessment of patients with a vocal fold implant by multidisciplinary team specialized in airway management is crucial. The choice of best-fit endotracheal tube and technique of intubation can minimize the risk of implant displacement. The present investigation provides different options for airway management in the setting of vocal fold implants describing solutions for special situations such as lung isolation and difficult intubation. An algorithm is presented as a visual tool to help anesthesiologists who encounter such patients for safe airway management while preserving the vocal fold implants.